Photodepositing CdS on the Active Cyano Groups Decorated g‐C3N4 in Z‐Scheme Manner Promotes Visible‐Light‐Driven Hydrogen Evolution - Wang, Zhipeng; Wang, Zilin; Zhu, Xiaodi; Ai, Changzhi; Zeng, Yamei; Shi, Wenyan; Zhang, Xidong; Zhang, Haoran; Si, Hewei; Li, Jin; Wang, Cai‐Zhuang; Lin, Shiwei (Small (Weinheim an der Bergstrasse, Germany), 2021)
g‐C3N4/CdS heterojunctions are potential photocatalysts for hydrogen production but their traditional type‐II configuration generally leads to weak oxidative and reductive activity. How to construct the novel Z‐scheme g‐C3N4/CdS counterparts to address this issue remains a great challenge in this field. In this work, a new direct Z‐scheme heterojunction of defective g‐C3N4/CdS is designed by introducing cyano groups (NC‐) as the active bridge sites. Experimental observations in combination with density functional theory (DFT) calculations reveal that the unique electron‐withdrawing feature of cyano groups in the defective g‐C3N4/CdS heterostructure can endow this photocatalyst with numerous advantageous properties including high light absorption ability, strong redox performance, satisfactory charge separation efficiency, and long lifetime of charge carriers. Consequently, the resultant photocatalytic system exhibits more active performance than CdS and g‐C3N4 under visible light and reaches an excellent hydrogen evolution rate of 1809.07 µmol h−1 g−1, which is 6.09 times higher than pristine g‐C3N4. Moreover, the defective g‐C3N4/CdS photocatalyst maintains good stability after 40 h continuous test. This work provides new insights into design and construction of Z‐scheme heterojunctions for regulating the visible‐light‐induced photocatalytic activity for H2 evolution. A direct Z‐scheme heterojunction of defective g‐C3N4/CdS is designed by introducing cyano groups as the active bridge sites. The specific electron‐withdrawing characteristic of cyano groups is conductive to promoting the intimate contact of the two components, providing a stable channel for the charge transfer from g‐C3N4 to CdS. Consequently, the defective g‐C3N4/CdS exhibits high hydrogen evolution activity under visible light.